Minimizing Ambiguity and Paraconsistency. - Vanackere, Guido (Logique et Analyse, 1999)
Ambiguity-adaptive logics offer a natural and rich formal solution to (possibly) inconsistent theories. Three views on ambiguities result in three different, intuitively correct ambiguity-adaptive logics with interesting applications. We present their semantics and proof theory, and illustrate that ambiguity-adaptive logics form an excellent alternative to paraconsistent logics that focus on the characteristics of the logical constants.